The Influence of Cultural Characteristics, Commitment and Work Stress on Employee Performance at PT. Earth of Concrete Facilities (BSB-Kalla Group) - Hastuti Mulan (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This study aims to analyze the effects of cultural characteristics, commitment, and work stress on the performance of employees of PT BSB Kalla Group. This type of quantitative research has a sample of 70 respondents with a full sampling technique. Data collection techniques consisted of interviews, observations, and questionnaires, as well as literature reviews and research results related to research. Data analysis consisted of descriptive statistical tests, data quality tests, classical assumption tests, hypothesis tests, and determinant coefficient tests (R2). The results of the study found that cultural characteristics had a significant effect on employee performance. Furthermore, commitment has a significant effect on employee performance. Job stress has a significant effect on employee performance. Variables of cultural characteristics, commitment, and work stress together have a significant effect on the performance of permanent employees. The results of this study can contribute to insight and understanding of things that can affect the performance of permanent employees. Based on this research, it is also expected that PT. BSB Kalla Group must consistently maintain good cultural characteristics for employees, be committed to carrying out their duties and obligations, and pay close attention to the work stress conditions of an employee.